Peran Pembinaan dan Pengawasan Pemerintah Daerah Malang Dalam Meningkatkan Kualitas Pelayanan Publik - Putri Theresia; Agitha Amelia Tambunan; Kellyna Najwa Julyanti; Keisya Vania Putri Satuhu; Ivan Dermawan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This research is motivated by challenges in monitoring and developing public services in the Malang Regional Government which require an integrated approach. Investments in human resource development and information technology are needed to increase the efficiency and effectiveness of supervision. Increasing the budget for guidance and supervision, strengthening the independence of supervisory institutions, and utilizing information technology are considered solutions to improve the quality of public services. The research method used in this research is a qualitative method with a literature study approach. This approach was chosen because it allows researchers to explore and understand the phenomenon of coaching and supervision in the context of public services through analysis of various relevant sources of information. The qualitative method focuses on an in-depth understanding of the existing context, processes and dynamics, making it suitable for studying the role of coaching and supervision in improving the quality of public services in the Malang Regional Government. Literature study as part of this qualitative method involves collecting and analyzing data from various sources such as books, academic journals, official government reports, and related policy documents. The research results show that guidance and supervision in the Malang Regional Government has an important role in improving the quality of public services. Coaching is carried out to increase the capacity and performance of state civil servants, while supervision aims to ensure employee compliance with applicable regulations. The main challenges faced are limited human and technological resources. Suggested solutions include investing in human resource development, increasing the budget for guidance and supervision, strengthening the independence of supervisory institutions, and utilizing information technology to increase the efficiency and effectiveness of supervision.